Pelvic floor muscle function is an independent predictor of outcome after retrourethral transobturator male sling procedure - Soljanik, Irina (World journal of urology, 2015)
PurposeTo evaluate the impact of the retrourethral transobturator sling (RTS) on pelvic floor muscle function (PFMF) and whether preoperative PFMF is associated with RTS outcome.MethodsBetween May 2008 and December 2010, 59 consecutive men with postprostatectomy stress urinary incontinence (PSUI) underwent PFMF assessment before RTS and 6 months thereafter in a prospective cohort study. The assessments included demographic and clinical characteristics, and quality of life (QoL) questionnaires. PFMF was evaluated by digital rectal examination on the modified 6-point Oxford scale and by surface electromyography. The primary outcome measurement was success after RTS defined as PSUI cure with use of no or one dry “security” pad. For secondary outcome, PFMF, 1-h pad test, and impact of PSUI on QoL were evaluated. Uni- and multivariate analyses were performed.ResultsAfter 6-month follow-up, the cure, improvement (>50 % pad reduction) and failure rates were 50 % (29/58 patients), 24 % (14/58 patients) and 26 % (15/58 patients), respectively. Significant improvement of QoL, clinical and PFMF parameters occurred after RTS. On multivariate analysis, weak PFMF (OR 86.29) and greater muscle fatigue (OR 3.31) were significant independent predictors of RTS failure. The final model demonstrated good calibration (p = 0.882) and excellent discriminative ability (0.942, 95 % CI 0.883-1.0) to predict success after RTS.ConclusionsPFMF improved significantly after RTS procedure. Higher muscle fatigue and weak PFMF were independent predictors of RTS failure. Digital rectal evaluation of PFMF is a simple and reliable clinical tool, which can be used by urologists in daily routine to predict the RTS outcome.